Teacher's Pedagogical Moves That Support Religion Children with Special Needs in Inclusion Classes - Toifur Toifur (Ijtimā iyya Journal of Muslim Society Research, 2021)
Religion is part of human rights. The books of ushul fiqh describe five basic principles in religion that must always be guarded, including maintaining religion. Law Number 20 of 2003 concerning the national education system provides full guarantee for children with special needs to get quality education services. The purpose of this study was to describe teacher learning actions that support the religious development of students with special needs in the inclusive class. The approach used in this study is a qualitative approach. The data sources in this study were the principal, teachers, and the person in charge of the inclusive class. Data collection was carried out in the inclusion class. In general, this data collection is carried out in two stages, namely simultaneous observation and interviews, as well as sudden observation and interviews. Simultaneous observation and interviews were carried out in order to collect data until it really met the completeness of the description and which was the focus of the research, while sudden observation and interviews were carried out in order to complete the missing data and in the framework of triangulation. Furthermore, recording and documentation were also carried out to complement the research data. Data analysis activities in this study were carried out inductively. Inductive data analysis was performed to find inferences / final conclusions on the data collected little by little from the research location. In analyzing the research data, the researcher used a data analysis framework adapted from the interactive model developed by Miles and Huberman (1992), which consists of four stages, namely: (1) data collection stage, (2) data reduction, (3) ) data presentation, and (4) data verification and drawing final conclusions. The results showed that teacher learning actions that support the diversity of students with special needs at SD Al Iesyad 02 Cilacap are translated through the integration of religious development through thematic learning and Islamic Education subjects supported by an inclusive team incorporated in the Butterfly Learning Center. To support this program, the community academics creates situations that support the achievement of instructional learning objectives and the impact that accompanies them. Creation of bi'ah islamiyah (Islamic environment) in schools. A comfortable and attractive classroom arrangement, installation of evocative and religious posters.